2002
DOI: 10.1385/mo:19:2:71
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients Undergoing Chemotherapy Show Adequate Serological Response to Vaccinations Against Influenza Virus and Streptococcus pneumoniae

Abstract: Cancer patients receiving chemotherapy are prone to develop infections that might postpone treatment and lead to complications. The aim of our study was to investigate whether a heterogeneous population of patients with solid tumors and malignant lymphoma undergoing chemotherapy would respond serologically to vaccination against influenza and pneumococcal disease. There are no established routines in oncology departments in Norway regarding vaccination of these patients. The study included 35 cancer patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 26 publications
4
63
0
2
Order By: Relevance
“…6 It has been shown that lymphoma patients treated with conventional chemotherapy alone may respond adequately to influenza vaccinations. [7][8][9][10] Rituximab may dramatically impair the humoral response to vaccination in rheumatoid arthritis patients, 11 but only a few studies have addressed this effect in rituximab-treated lymphoma patients. [12][13][14] We have conducted a controlled study where serologic response to the influenza A (H1N1) virus vaccine Pandemrix during the 2009 "swine flu" pandemic was analyzed in 67 lymphoma patients treated with rituximab monotherapy or in combination with chemotherapy within the last 6 months before vaccination and compared it with the response in 51 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been shown that lymphoma patients treated with conventional chemotherapy alone may respond adequately to influenza vaccinations. [7][8][9][10] Rituximab may dramatically impair the humoral response to vaccination in rheumatoid arthritis patients, 11 but only a few studies have addressed this effect in rituximab-treated lymphoma patients. [12][13][14] We have conducted a controlled study where serologic response to the influenza A (H1N1) virus vaccine Pandemrix during the 2009 "swine flu" pandemic was analyzed in 67 lymphoma patients treated with rituximab monotherapy or in combination with chemotherapy within the last 6 months before vaccination and compared it with the response in 51 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…These patients would be ideal candidates for active immunization. Even patients undergoing chemotherapy have been shown to demonstrate adequate antibody responses to polysaccharide, protein, and conjugated vaccines (7,8,33). The vaccination strategy could also be optimized to function in a T cell-independent fashion through adjuvants of conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…of chemotherapy has been shown to protect them through periods of immunosuppression (7)(8)(9). Pneumocystis is an attractive target for vaccine-based prevention, since patient populations at risk for PcP can often be identified prior to patients becoming immunosuppressed.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][39][40][41] We examined B-cell and T-cell recovery kinetics to understand the landscape of the immune system after ASCT. It is clear that the provision of the autologous T-cell product led to rapid quantitative reconstitution of both the B-cell and T-cell compartments ( Figures 3 and 4).…”
Section: B-cell and T-cell Recovery Kineticsmentioning
confidence: 99%